Composition and behavior of sunflower seeds (Helianthus annuus l.) from plants treated with magnetic fields for energy potential use of biomass (2023)
Undoubtedly, with the different effects of climate change, the companies producing biofuels have turned their attention to the woody and herbaceous species, for their energy use. Although these processes are based on the different agroindustry chains that are developed at local, regional, national or international level, depending on the type of soil, vegetation and predominant climate presented in each of them. For this reason, the industry transformation sector must go hand in hand with the primary sector, ensuring a large amount of volume in the production of biomass with characteristics desired by the processors of plants for the use of bioenergy improving the production techniques. Having said that, this research evaluated the composition and initial behavior in a second generation of the sunflower seeds (Helianthus annuss L.) of plants that were treated during their germination phase with induced magnetic fields. The magnetic field strengths of 14µT and 422µT to which the mother plants were subjected were generated with coils of 300 and 1200 turns, handling an exposure time of 60 min, 180 min, 300 min and 15 days (permanent). Subsequently evaluating seeds in relation to variables such as germination and initial seedling growth (% of germination, fresh biomass and dry biomass, leaf area, chlorophyll, in addition, to development indicators); in the same way, the watery activity, the protein nitrogen content, the ethereal extract or crude fat content, the ash content and the crude fiber were determined on the seeds of the first generation. On the other hand, the experimental design was subject to the initial conditions of culture of the mother plants being a factorial design in relation two components "field intensity x time of magnetic induction". The best results were evidenced in those plants coming from seeds of mother plants treated with fields with lower intensity and with a longer exposure time. Copyright © 2018, AIDIC Servizi S.r.l.